Polishing sheet and method for manufacturing semiconductor device using the same

By using a laminated grinding sheet composed of a grinding layer, an adhesive layer and a liner layer in the chemical mechanical grinding sheet, and adjusting its initial load resistance and compression elasticity, the problem that existing grinding sheets are difficult to control grinding characteristics during grinding, achieving efficient grinding rate and flatness, and providing high-quality semiconductor devices.

CN113410163BActive Publication Date: 2025-04-04SK ENPULSE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110287225.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-03-17
Publication Date
2025-04-04
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

During the grinding process, it is difficult to effectively control the compression and wetting characteristics of the grinding layer, liner layer and laminated body, resulting in poor grinding characteristics and prone to scratches and uneven grinding problems.

Method used

A laminated body grinding sheet composed of a grinding layer, an adhesive layer and a liner layer is used to optimize the grinding performance by adjusting the initial load resistance and compression elasticity of the laminated body. The specific method includes introducing a urethane polymer as the abrasive layer material in the abrasive sheet and bonding the abrasive layer and the liner layer together by a hot melt adhesive.

Benefits of technology

By controlling the resistance characteristics and compression elastic properties of the laminated body, the grinding rate and grinding flatness are significantly improved, scratches and grinding uneven phenomena are reduced, and high-quality semiconductor devices are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113410163B_ABST
    Figure CN113410163B_ABST
Patent Text Reader

Abstract

The present invention relates to a polishing sheet used in the chemical mechanical polishing (CMP) process of a semiconductor device. In the above-mentioned polishing sheet, excellent polishing rate and polishing flatness can be ensured by controlling the initial load resistance, compression modulus and other physical properties of the liner layer and / or the stack defined by Formulas 1 and 2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] An embodiment of the present invention relates to a polishing sheet used in a chemical mechanical polishing process of a semiconductor device. Background Art

[0002] Recently, the semiconductor market has further expanded, and the use of chemical mechanical polishing sheets has also increased. Chemical mechanical polishing sheets are polishing sheets used in the chemical mechanical polishing (CMP) process of polishing the surface of semiconductor substrates such as wafers by chemical mechanical methods, and are one of the important process factors that determine the final surface characteristics of semiconductor substrates.

[0003] In the semiconductor manufacturing process, the chemical mechanical polishing process is a process in which a slurry is supplied to induce a chemical reaction on the surface of the semiconductor substrate while the semiconductor substrate is attached to a head and in contact with the surface of a polishing sheet formed on a platen, and the concave and convex parts of the surface of the semiconductor substrate are mechanically polished by causing the platen and the head to move relative to each other.

[0004] In this chemical mechanical polishing process, the semiconductor substrate is polished in a state where a predetermined pressure is applied to the surface of the polishing sheet, and polishing is performed in a wet environment by adding polishing slurry. Therefore, among the multiple factors that can determine the surface properties of the semiconductor substrate, the compression property and the wetting property of the polishing sheet become one of the most important factors.

[0005] Therefore, there is a continuous demand for research on how to improve the polishing characteristics of the chemical mechanical polishing process by controlling multiple physical properties related to the compression characteristics and wetting characteristics of the polishing layer, the cushion layer and / or the laminate.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Korean Patent Publication No. 1107842 Summary of the invention

[0009] The present invention provides a polishing sheet having excellent polishing characteristics such as polishing rate and polishing flatness for silicon oxide and tungsten.

[0010] An example of an abrasive sheet includes a laminate composed of an abrasive layer, an adhesive layer, and a cushion layer. The initial load resistance LR of the laminate is defined by the following formula 1: L More than 88%,

[0011] <Formula 1>

[0012]

[0013] In the above formula 1, T1 L is the thickness of the laminate under no-load conditions, T2 L T3 is the thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. L From the above T2 L The thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds.

[0014] Another example of an abrasive sheet includes an abrasive layer and a cushion layer, wherein the cushion layer has an initial load resistance LR defined by the following formula 5: C More than 45%,

[0015] <Formula 5>

[0016]

[0017] In the above formula 5, T1 C is the thickness of the cushion layer under no-load condition, T2 C T3 is the thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. C From the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds.

[0018] Another example of a method for manufacturing a semiconductor device includes: preparing a lapping sheet including a laminate composed of a lapping layer, an adhesive layer, and a cushion layer; and relatively rotating the lapping sheet so that the lapping layer surface contacts the surface of a wafer and thereby lapping the surface of the wafer, wherein the initial load resistance LR of the laminate defined by the above formula 1 is L It is more than 88%.

[0019] The polishing sheet according to the example can ensure excellent polishing rate and polishing flatness by controlling the physical properties of the backing layer and / or the laminate, such as the electrical resistance characteristics and the compressive elasticity characteristics.

[0020] Therefore, if the polishing sheet of the embodiment of the present invention is used, the occurrence of scratches and other defects on the polishing object can be reduced, uneven polishing can be suppressed, polishing precision can be improved, and high-quality semiconductor devices can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic process diagram showing an example of a semiconductor device manufacturing process.

[0022] [Description of Reference Numerals]

[0023] 110: grinding sheet 120: fixed plate

[0024] 130: semiconductor substrate 140: nozzle

[0025] 150: polishing slurry 160: polishing head

[0026] 170: Regulator DETAILED DESCRIPTION

[0027] Hereinafter, examples are described in detail with reference to the accompanying drawings to facilitate those skilled in the art to which the present invention belongs to implement the present invention. However, examples of the present invention can be embodied in a variety of different implementations, which are not limited to the examples described in this specification.

[0028] In the present specification, when a part is expressed to “include” a certain structural element, unless there is any special description to the contrary, this means that other structural elements may be included, rather than excluding other structural elements.

[0029] In this specification, unless otherwise specified, an expression in the singular should be interpreted as including the expression in the singular or plural in the text.

[0030] Furthermore, unless otherwise specified, all numbers and expressions indicating amounts of constituent components, reaction conditions, and the like described in the present specification should be understood to be modified by the term "about" in all cases.

[0031] <Abrasive Sheet>

[0032] One embodiment of the present invention provides a polishing sheet having excellent polishing characteristics such as polishing rate and polishing flatness for tungsten.

[0033] An example of an abrasive sheet includes a laminate composed of an abrasive layer, an adhesive layer, and a cushion layer. The initial load resistance LR of the laminate is defined by the following formula 1: L It is more than 88%.

[0034] <Formula 1>

[0035]

[0036] In the above formula 1, T1 L is the thickness of the laminate under no-load conditions, T2 L T3 is the thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. L From the above T2 L The thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds.

[0037] Specifically, the initial load resistance LR of the laminate is LThe percentage may be 88.5% or more, 89% or more, 89.5% or more, 90% or more, 90.5% or more, 91% or more, 88% to 98%, 88% to 97%, 88% to 96%, 90% to 98%, or 91% to 97%, but is not limited thereto.

[0038] The above initial load resistance LR L It is a value that parametrically expresses the ratio of the thickness change degree of the laminate when a weaker force and a stronger force are applied.

[0039] Initial load resistance LR L The polishing sheet using the laminate satisfying the above range can minimize scratches on the polishing object and form a supporting force capable of ensuring excellent polishing performance.

[0040] If the abrasive sheet uses the initial load resistance LR L If the laminate exceeds the above range, scratches may be generated on the polishing object, thereby reducing the quality of the polishing object, or reducing the polishing performance such as the polishing rate and polishing flatness.

[0041] That is, the initial load resistance LR of the laminate can be L By satisfying the above range, scratches on the polishing object caused by the manufactured polishing sheet can be minimized. Moreover, due to the excellent polishing rate and polishing flatness, it is convenient to polish materials that require high surface flatness, such as silicon wafers for semiconductor devices.

[0042] The compressive modulus CE of the laminated body included in the polishing sheet of another example is defined by the following formula 2: L More than 50%.

[0043] <Formula 2>

[0044]

[0045] In the above formula 2, T2 L T3 is the thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. L From the above T2 L The thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds, T4 L For the above T3 L The state is the thickness of the laminate when the stress load is released and the laminate is left for 60 seconds and then the stress load of 30 kPa is maintained for 60 seconds.

[0046] Specifically, the compressive modulus CE of the laminate is LIt can be more than 55%, more than 58%, more than 60%, more than 63%, more than 65%, more than 68%, more than 70%, 50% to 98%, 60% to 98%, 65% to 98%, 70% to 98%, 60% to 95%, 70% to 95%, 70% to 92%, but is not limited to these.

[0047] The above compression modulus CE L This is a parameter value related to the degree of recovery after a strong force is applied to the laminate composed of the polishing layer, the adhesive layer and the cushion layer for a specified period of time.

[0048] The compression elasticity CE L The polishing sheet in which the laminate satisfying the above range is used can minimize scratches generated on the polishing object and can ensure polishing performance of a prescribed level or more even after long-term use.

[0049] If the grinding sheet uses the compression elasticity CE L If the pad layer exceeds the above range, the grinding performance may be uneven, for example, the grinding performance may drop sharply after long-term use, etc. Alternatively, the quality of the grinding object may be reduced due to scratches on the grinding object.

[0050] That is, the compressive elastic modulus CE of the laminate can be L By satisfying the above range, the generation of scratches and other wear on the polishing object by the polishing sheet can be minimized, the polishing performance can be maintained at a constant level, and excellent polishing rate and polishing flatness can be ensured.

[0051] The initial load resistance LR of the laminate can be designed by adjusting the material and composition of the laminate. L And compression elasticity CE L It can also be designed by comprehensively adjusting the mechanical properties, physical structure, manufacturing process conditions, post-processing conditions, storage / aging conditions, etc. of the polishing layer, bonding layer and cushion layer included in the above-mentioned laminate.

[0052] The polishing sheet according to the example of the present invention includes a laminated body, and the laminated body is composed of a polishing layer, an adhesive layer, and a cushion layer.

[0053] The polishing layer is polished in a manner facing the semiconductor substrate during the polishing step.

[0054] The grinding layer may include a carbamate polymer. The carbamate polymer may be formed by a curing reaction of a carbamate prepolymer and a curing agent. Specifically, the grinding layer may include a cured product of a composition in which a carbamate prepolymer, a curing agent and a foaming agent are included, but is not limited thereto.

[0055] The above-mentioned prepolymer generally refers to a polymer with a relatively low molecular weight that is retained in an intermediate stage in order to facilitate the molding of the final product. Such a prepolymer can be molded by itself or after reacting with other polymerizable compounds.

[0056] Specifically, the urethane prepolymer comprises a prepolymerization reaction product of one or more isocyanate compounds and one or more polyols. Furthermore, the urethane prepolymer is prepared by the reaction of an isocyanate compound and a polyol, and may contain unreacted isocyanate groups (NCO). As long as they can be used for the preparation of urethane polymers, the isocyanate compound and the polyol compound are not particularly limited.

[0057] The isocyanate compound used in the preparation of the above prepolymer can be selected from toluene diisocyanate (TDI), 1,5-naphthalene diisocyanate (naphthalene-1,5-diisocyanate), p-phenylene diisocyanate (p-phenylene diisocyanate), tolidine diisocyanate, 4,4'-diphenyl methane diisocyanate (4,4'-diphenyl methane diisocyanate), hexamethylene diisocyanate (hexamethylene diisocyanate, HDI), dicyclohexylmethane diisocyanate (dicyclohexylmethane diisocyanate), methylene diisocyanate (methylene diisocyanate), ... diphenyldiisocyanate (MDI), 1-isocyanato-4-[(4-isocyanatocyclohexyl)methyl]cyclohexan (1-isocyanato-4-[(4-isocyanatocyclohexyl)methyl]cyclohexan (H12MDI) and isophorone diisocyanate (isophorone diisocyanate) The group consisting of one or more isocyanates, but is not limited thereto.

[0058] Furthermore, the polyol used for preparing the above-mentioned prepolymer means a compound having two or more hydroxyl groups, and may include a polymer polyol and a monomolecular polyol.

[0059] For example, the polymer polyol may be one or more polyols selected from the group consisting of polyether polyol, polyester polyol, polycarbonate polyol, and polycaprolactone polyol. The weight average molecular weight (Mw) of the polymer polyol may be 300 g / mol to 3000 g / mol.

[0060] Examples of the monomolecular polyol include at least one selected from the group consisting of ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), 1,3-propanediol (PDO) and 2-methyl-1,3-propanediol (MP-diol), but are not limited thereto.

[0061] The isocyanate terminal group content (NCO%) of the urethane prepolymer may be 6 weight percent to 12 weight percent, 6 weight percent to 11 weight percent, 6 weight percent to 10 weight percent, or 8 weight percent to 10 weight percent.

[0062] The weight average molecular weight (Mw) of the urethane prepolymer may be in the range of 300 g / mol to 3000 g / mol, 500 g / mol to 2500 g / mol, or 700 g / mol to 2000 g / mol.

[0063] The curing agent may be one or more selected from the group consisting of amine compounds and alcohol compounds. Specifically, the curing agent may include one or more compounds selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.

[0064] For example, the curing agent may be selected from 4,4'-methylenebis(2-chloroaniline) (MOCA), diethyltoluenediamine (DETDA), 4,4'-diamino-3,3'-dichlorodiphenylmethane (bis(4-amino-3-chlorophenyl)methane), diaminodiphenyl methane, diaminodiphenyl sulfone, m-xylylene diamine, isophorone diamine, At least one selected from the group consisting of butylene glycol, butylene glycol, hexanediol, glycerine and trimethylolpropane.

[0065] The foaming agent is not particularly limited as long as it is a foaming agent commonly used to form pores in a polishing sheet. For example, the foaming agent may be one or more selected from a solid-phase foaming agent having a hollow structure, a liquid-phase foaming agent using a volatile liquid, and a gas-phase foaming agent such as an inert gas. Specifically, the foaming agent may be one or more selected from the group consisting of a solid-phase foaming agent and a gas-phase foaming agent, but is not limited thereto.

[0066] The solid-phase foaming agent may be a microcapsule whose size is adjusted by thermal expansion (hereinafter referred to as "thermally expanded microcapsule"). The thermally expanded microcapsule may be obtained by heating and expanding a thermally expandable microcapsule. The thermally expanded microcapsule is an expanded microballoon structure with a uniform diameter, and has the advantage that the diameter of the pores can be uniformly adjusted. Specifically, the solid-phase foaming agent may be a microballoon structure with an average diameter of 5 μm to 200 μm.

[0067] The thermally expandable microcapsule may include: an outer skin including a thermoplastic resin; and a foaming agent encapsulated inside the outer skin. The thermoplastic resin may be one or more selected from the group consisting of vinylidene chloride copolymers, acrylonitrile copolymers, methacrylonitrile copolymers, and propylene copolymers. Furthermore, the foaming agent may be one or more selected from the group consisting of hydrocarbons having 1 to 7 carbon atoms.

[0068] The solid-phase foaming agent may be contained in an amount of 0.1 to 3.0 parts by weight based on 100 parts by weight of the urethane prepolymer. Specifically, the solid-phase foaming agent may be contained in an amount of 0.5 to 2.5 parts by weight or 0.8 to 2.2 parts by weight based on 100 parts by weight of the urethane prepolymer.

[0069] The gas phase foaming agent may contain an inert gas, and the type of the inert gas is not particularly limited as long as it is a gas that does not participate in the reaction between the urethane prepolymer and the epoxy curing agent. For example, the inert gas may be one or more selected from the group consisting of nitrogen gas (N2), carbon dioxide gas (CO2), argon gas (Ar) and helium (He). Specifically, the inert gas may be nitrogen gas (N2) or carbon dioxide gas (CO2).

[0070] The inert gas may be added in an amount of 10% to 30% by volume relative to the total volume of the composition. Specifically, the inert gas may be added in an amount of 15% to 30% by volume relative to the total volume of the composition.

[0071] The above composition may optionally further comprise a surfactant.

[0072] The surfactant can prevent the overlapping and superposition of the formed multiple holes. Specifically, the surfactant is suitable for using a silicon-based nonionic surfactant, but in addition, it can be selected in a variety of ways according to the physical properties required by the polishing sheet.

[0073] The above-mentioned silicon-based nonionic surfactant may be used alone or in combination with a silicon-based nonionic surfactant not having a hydroxyl group.

[0074] The silicon-based nonionic surfactant having the above hydroxyl group is not particularly limited as long as it is widely used in the field of polyurethane technology due to its excellent compatibility with isocyanate-containing compounds and active hydrogen compounds. For example, commercially available materials of the silicon-based nonionic surfactant having the above hydroxyl group include DOW CORNING 193 (silicone glycol copolymer, liquid phase; specific gravity at 25°C reaches 1.07; viscosity at 20°C reaches 465 mm 2 / s; ignition point reaches 92°C) (hereinafter referred to as DC-193), etc.

[0075] For example, commercially available materials of silicon-based nonionic surfactants without the above hydroxyl groups include DOW CORNING 190 (silicone glycol copolymer, Gardner color scale: 2; specific gravity at 25°C reaches 1.037; viscosity at 25°C reaches 2000 mm 2 / s; flash point reaches 63°C or above; inverse solubility point (1.0% aqueous solution) reaches 36°C) (hereinafter referred to as DC-190), etc.

[0076] The surfactant may be contained in an amount of 0.1 to 2.0 parts by weight based on 100 parts by weight of the urethane prepolymer. Specifically, the surfactant may be contained in an amount of 0.2 to 1.5 parts by weight based on 100 parts by weight of the urethane prepolymer. When the content of the surfactant reaches the above range, the pores caused by the gas-phase foaming agent can be stably formed and maintained in the mold.

[0077] The thickness of the above grinding layer L Specifically, the average thickness of the grinding layer may be 0.5 mm to 4.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 3.0 mm, 1.7 mm to 2.7 mm, or 2.0 mm to 3.5 mm.

[0078] The hardness of the above grinding layer L It can be 30ShoreD to 80ShoreD. Specifically, the hardness of the grinding layer is L It may be 40ShoreD to 80ShoreD, 50ShoreD to 80ShoreD, 40ShoreD to 70ShoreD, 50ShoreD to 70ShoreD, 55ShoreD to 65ShoreD, but is not limited thereto.

[0079] The above-mentioned grinding layer may include a plurality of pores. In this case, the average size of the pores is L The average size of the pores may be 5 μm to 50 μm. L The thickness may be 5 μm to 40 μm, 10 μm to 40 μm, or 10 μm to 30 μm, but is not limited thereto.

[0080] The cushion layer supports the polishing layer and absorbs and disperses impact applied to the polishing layer.

[0081] The cushion layer may include non-woven fabric or suede, but is not limited thereto.

[0082] In one example, the cushion layer may be a resin-impregnated nonwoven fabric. The nonwoven fabric may be a fiber nonwoven fabric containing one selected from the group consisting of polyester fiber, polyamide fiber, polypropylene fiber, polyethylene fiber, and a combination thereof.

[0083] The resin impregnated in the above-mentioned non-woven fabric may include one selected from the group consisting of polyurethane resin, polybutadiene fiber, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, polyamide elastomer resin and combinations thereof.

[0084] The thickness of the above-mentioned cushion layer L The thickness of the cushion layer can be 0.5 mm to 2.5 mm. L It may be 0.8 mm to 2.5 mm, 1.0 mm to 2.5 mm, 1.0 mm to 2.0 mm, 1.2 mm to 1.8 mm, 1.2 mm to 1.5 mm, or 1.2 mm to 1.4 mm, but is not limited thereto.

[0085] The hardness of the cushion layer L It can be 68AskerC to 74AskerC, 69AskerC to 74AskerC, 70AskerC to 74AskerC, 71AskerC to 74AskerC, but is not limited thereto.

[0086] The density of the above-mentioned cushion layer L It can be about 0.1 g / cm 3 To about 0.6g / cm 3 , for example, can be about 0.1 g / cm 3 To about 0.5g / cm 3 , for example, can be about 0.1 g / cm 3 To about 0.4g / cm 3 , for example, can be about 0.2 g / cm 3 To about 0.4g / cm 3 .

[0087] For the above-mentioned cushion layer, the initial thickness D1 was measured. L , measure the thickness D2 after 3 minutes of pressure with 800g weight L Then the thickness D3 was measured after 1 minute of recovery time. L In this case, the compression rate of the above-mentioned cushion layer is derived from the following formula 3: LIt may be about 5% to about 15%, for example, it may be about 8% to about 14%, for example, it may be about 10% to about 14%.

[0088] <Formula 3>

[0089] Compression L (%)=(D1 L -D2 L ) / D1 L ×100

[0090] For the above-mentioned cushion layer, the initial thickness D1 was measured. L , measure the thickness D4 after 1 minute of pressure with 800g weight L Then the thickness D5 was measured after 1 minute of recovery time. L In this case, the elastic modulus of the cushion layer is derived from the following formula 4: L It may be about 91%, for example, it may be about 65% to about 91%, for example, it may be about 70% to about 91%, for example, it may be about 80% to about 90%.

[0091] <Formula 4>

[0092] Elasticity L (% = (D5 L -D4 L ) / (D1 L -D4 L )×100

[0093] The above-mentioned laminate satisfies the initial load resistance LR defined by the above-mentioned <Formula 1> in the above-mentioned range. L And the compression modulus CE defined by the above <Formula 2> L At the same time, the liner layer satisfies the compression ratio defined by <Formula 3> in the above range. L And the elastic modulus defined by <Equation 4> L In the case of abrasive layer, the above-mentioned grinding layer can be stacked together to achieve the desired grinding performance. The above-mentioned initial load resistance LR can be designed by adjusting the materials and composition of the above-mentioned cushion layer and the laminate. L , compression elasticity CE L , compression ratio L And elasticity L It can also be designed by comprehensively adjusting the manufacturing process conditions, post-processing conditions, storage / aging conditions, etc. of the above-mentioned cushion layer.

[0094] The laminated body included in the polishing sheet of the embodiment of the present invention may be composed of a polishing layer, a bonding layer and a cushion layer, and the bonding layer may be located between the polishing layer and the cushion layer.

[0095] Furthermore, the adhesive layer may include a hot melt adhesive.

[0096] The hot melt adhesive may be one or more selected from the group consisting of polyurethane resin, polyester resin, ethylene-vinyl acetate resin, polyamide resin and polyolefin resin. Specifically, the hot melt adhesive may be one or more selected from the group consisting of polyurethane resin and polyester resin.

[0097] Elastic modulus of the abrasive sheet of the present invention L Can be 100kgf / cm 2 Up to 160kgf / cm 2 Specifically, the elastic modulus of the above-mentioned grinding sheet is L Can be 100kgf / cm 2 Up to 150kgf / cm 2 、100kgf / cm 2 Up to 140kgf / cm 2 、100kgf / cm 2 Up to 130kgf / cm 2 , but is not limited to this.

[0098] When the above modulus L When the above range is reached, a polishing sheet having a high polishing speed and high polishing flatness characteristics and uniformity can be provided.

[0099] Furthermore, the abrasive sheet of the above example includes a laminate composed of a polishing layer, a bonding layer and a cushion layer, and the laminate satisfies the initial load resistance LR within the above range. L And compression elasticity CE L .

[0100] The abrasive sheet of the present invention can be made to have an initial load resistance LR of the laminated body. L And compression elasticity CE L The above range is achieved by controlling the grinding process to ensure excellent grinding rate and grinding flatness.

[0101] The thickness T1 of the laminated body under no load L Specifically, the thickness T1 of the laminated body under no load is 2.0 mm to 4.5 mm. L It can be 2.0mm to 4.2mm, 2.5mm to 4.2mm, 2.8mm to 4.2mm, 3.0mm to 4.0mm, 3.2mm to 3.8mm, 3.2mm to 3.6mm, but is not limited thereto.

[0102] The grinding rate of the grinding sheet of the present invention for tungsten W can be The grinding thickness of silicon wafers can be divided according to the grinding time (minutes). To obtain the above grinding rate

[0103] Specifically, the grinding rate of the above-mentioned grinding sheet for tungsten W can be to to to to to to to to However, the present invention is not limited thereto.

[0104] When the polishing rate of the polishing sheet exceeds the above range, there is a possibility that defects such as scratches may be generated on the polishing object or the polishing performance may be reduced.

[0105] Furthermore, the polishing sheet of the present invention can achieve a polishing flatness (WIWNU) of 4.3% or less for tungsten W. The polishing flatness can be obtained by the following formula.

[0106]

[0107] Specifically, the polishing flatness of the above-mentioned polishing sheet for tungsten W may be 5.5% or less, 4.2% or less, 4.1% or less, 4.0% or less, or 3.9% or less, but is not limited thereto.

[0108] If the polishing flatness of the polishing sheet reaches the above range, it is easy to polish the surface of the polishing object that requires high surface flatness, and a semiconductor device with excellent quality can be provided.

[0109] The constituent components and physical properties of the above-mentioned polishing sheets can be combined with each other.

[0110] Another embodiment provides a polishing sheet having excellent polishing properties such as polishing rate and polishing flatness for silicon oxide.

[0111] Another example of an abrasive sheet includes an abrasive layer and a cushion layer, wherein the cushion layer has an initial load resistance LR defined by the following formula 5: C Reach more than 45%.

[0112] <Formula 5>

[0113]

[0114] In the above formula 5, T1 C is the thickness of the cushion layer under no-load condition, T2 CT3 is the thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. C For the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds.

[0115] Specifically, the initial load resistance LR of the cushion layer is C It may be more than 50%, more than 55%, more than 60%, more than 65%, more than 70%, more than 75%, 45% to 98%, 45% to 95%, 45% to 90%, 50% to 90%, 60% to 90%, 70% to 90%, but is not limited thereto.

[0116] The above initial load resistance LR C It is a value that parametrically expresses the ratio of the thickness change of the cushion layer when a weaker force and a stronger force are applied.

[0117] Initial load resistance LR C The polishing sheet in which the cushion layer satisfying the above range is used can minimize scratches generated on the polishing object and can form a supporting force capable of ensuring excellent polishing performance.

[0118] If the abrasive sheet uses the initial load resistance LR C If the pad layer exceeds the above range, scratches may be generated on the polishing object, thereby reducing the quality of the polishing object or reducing the polishing rate.

[0119] That is, the initial load resistance LR of the cushion layer can be C By satisfying the above range, scratches on the polishing object caused by the manufactured polishing sheet can be minimized. Moreover, due to the excellent polishing rate and polishing flatness, it is convenient to polish materials that require high surface flatness, such as silicon wafers for semiconductor devices.

[0120] The compressive elastic modulus CE of the cushion layer included in the polishing sheet of another example is defined by the following formula 6: C Reach less than 90%.

[0121] <Formula 6>

[0122]

[0123] In the above formula 6, T2 C T3 is the thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. C From the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds, T4 CFor the above T3 C The stress load is eliminated and after 60 seconds, the 30 kPa (300 g / cm 2 ) is the thickness of the cushion layer when the stress load is greater than .

[0124] Specifically, the compressive elastic modulus CE of the cushion layer is C It may be less than 89.8%, less than 88%, less than 80%, more than 10% and less than 90%, more than 20% and less than 90%, more than 30% and less than 90%, 40% and less than 90%, 20% to 85%, 20% to 80%, 30% to 80%, 40% to 80%, but is not limited to these.

[0125] The above compression modulus CE C It is a parameter value related to the degree of recovery after a strong force is applied to the cushion layer for a specified time.

[0126] The compression elasticity CE C The polishing sheet in which the cushion layer satisfying the above range is used can minimize scratches generated on the polishing object and can ensure polishing performance above a prescribed level even after long-term use.

[0127] If the grinding sheet uses the compression elasticity CE C If the pad layer exceeds the above range, scratches may be generated on the polishing object, resulting in a decrease in the quality of the polishing object, or uneven polishing performance may be caused.

[0128] That is, the compression modulus CE of the cushion layer can be C By satisfying the above range, the generation of scratches and other wear on the polishing object by the polishing sheet can be minimized, the polishing performance can be maintained at a constant level, and excellent polishing rate and polishing flatness can be ensured.

[0129] The abrasive sheet according to the example of the present invention includes an abrasive layer.

[0130] The polishing layer is polished in a manner facing the semiconductor substrate during the polishing step.

[0131] The grinding layer may include a carbamate polymer. The carbamate polymer may be formed by a curing reaction of a carbamate prepolymer and a curing agent. Specifically, the grinding layer may include a cured product of a composition in which a carbamate prepolymer, a curing agent and a foaming agent are included, but is not limited thereto.

[0132] The details of the prepolymer, curing agent and foaming agent are the same as those described above.

[0133] Furthermore, the composition may further optionally include a surfactant, and the details related to the surfactant are the same as those described above.

[0134] The thickness of the above grinding layer C Not particularly limited. Specifically, the average thickness of the above-mentioned grinding layer is C It can be 0.8mm to 5.0mm, 1.0mm to 4.0mm, 1.0mm to 3.0mm, 1.5mm to 3.0mm, 1.7mm to 2.7mm, 2.0mm to 3.5mm.

[0135] The hardness of the above grinding layer C It can be 30ShoreD to 80ShoreD. Specifically, the hardness of the grinding layer is C It may be 40ShoreD to 80ShoreD, 50ShoreD to 80ShoreD, 40ShoreD to 70ShoreD, 50ShoreD to 70ShoreD, 55ShoreD to 65ShoreD, but is not limited thereto.

[0136] The above-mentioned grinding layer may include a plurality of pores. In this case, the average size of the pores is C The average size of the pores may be 5 μm to 50 μm. C The thickness may be 5 μm to 40 μm, 10 μm to 40 μm, or 10 μm to 30 μm, but is not limited thereto.

[0137] The polishing sheet according to the example of the present invention includes a backing layer.

[0138] The cushion layer supports the polishing layer and absorbs and disperses impact applied to the polishing layer.

[0139] The cushion layer may include non-woven fabric or suede, but is not limited thereto.

[0140] The details regarding the type, composition, etc. of the cushion layer are the same as those described above.

[0141] The above-mentioned cushion layer satisfies the initial load resistance LR within the above range. C And compression elasticity CE C .

[0142] The abrasive sheet of the present invention can be obtained by adjusting the initial load resistance LR of the cushion layer. C And compression elasticity CE C Control within the above range to ensure excellent grinding rate and grinding flatness.

[0143] The thickness T1 of the cushion layer under no load CSpecifically, the thickness T1 of the cushion layer under no-load condition is C It may be 0.8 mm to 2.5 mm, 1.0 mm to 2.5 mm, 1.0 mm to 2.0 mm, 1.2 mm to 1.8 mm, or 1.2 mm to 1.4 mm, but is not limited thereto.

[0144] The initial load resistance LR of the cushion layer can be designed by adjusting the material and composition of the cushion layer. C And compression elasticity CE C It can also be designed by comprehensively adjusting the mechanical properties, physical structure, manufacturing process conditions, post-processing conditions, storage / aging conditions, etc. of the above-mentioned cushion layer.

[0145] In another example, the hardness of the cushion layer C The temperature may be 69AskerC to 80AskerC, 69AskerC to 78AskerC, or 69AskerC to 75AskerC, but is not limited thereto.

[0146] The density of the above-mentioned cushion layer C It can be about 0.1 g / cm 3 To about 0.6g / cm 3 , for example, can be about 0.1 g / cm 3 To about 0.5g / cm 3 , for example, can be about 0.1 g / cm 3 To about 0.4g / cm 3 , for example, can be about 0.2 g / cm 3 To about 0.4g / cm 3 .

[0147] For the above-mentioned cushion layer, the initial thickness D1 was measured. C , measure the thickness D2 after 3 minutes of pressure with 800g weight C Then the thickness D3 was measured after 1 minute of recovery time. C In this case, the compression rate of the above-mentioned cushion layer is derived from the following formula 7: C It may be about 5% to about 15%, for example, it may be about 8% to about 14%, for example, it may be about 10% to about 14%.

[0148] <Formula 7>

[0149]

[0150] For the above-mentioned cushion layer, the initial thickness D1 was measured. C , measure the thickness D4 after 1 minute of pressure with 800g weightC Then the thickness D5 was measured after 1 minute of recovery time. C In this case, the elastic modulus of the cushion layer is derived from the following formula 8: C It may be about 91% or less, for example, about 65% to about 91%, for example, about 70% to about 91%, for example, about 80% to about 90%.

[0151] <Formula 8>

[0152]

[0153] The cushion layer satisfies the initial load resistance LR defined by the above-mentioned <Formula 5> in the above-mentioned range. C And the compression modulus CE defined by the above <Formula 6> C At the same time, the liner layer satisfies the compression ratio defined by <Formula 7> in the above range. C And the elastic modulus defined by <Equation 8> C In the case of abrasive layer, the above-mentioned polishing layer can be stacked together to achieve the desired polishing performance. Not only can the above-mentioned initial load resistance LR be designed by adjusting the material and composition of the above-mentioned cushion layer, but also the above-mentioned initial load resistance LR can be designed by adjusting the material and composition of the above-mentioned cushion layer. C , compression elasticity CE C , compression ratio C And elasticity C It can also be designed by comprehensively adjusting the manufacturing process conditions, post-processing conditions, storage / aging conditions, etc. of the above-mentioned cushion layer.

[0154] The polishing sheet of the embodiment of the present invention further comprises a bonding layer between the polishing layer and the cushion layer. The bonding layer may comprise the same hot melt adhesive as described above, but is not limited thereto.

[0155] Elastic modulus of the abrasive sheet of the present invention C Can be 80kgf / cm 2 Up to 170kgf / cm 2 Specifically, the elastic modulus of the above-mentioned grinding sheet is C Can be 90kgf / cm 2 Up to 170kgf / cm 2 or 100kgf / cm 2 Up to 170kgf / cm 2 , but is not limited to this.

[0156] The polishing sheet of the present invention is for silicon oxide (SiO x ) can be The grinding thickness of silicon wafers can be divided according to the grinding time (minutes). To obtain the above grinding rate

[0157] Specifically, for silicon oxide (SiO x ) can be to to to to to to to However, the present invention is not limited thereto.

[0158] When the polishing rate of the polishing sheet exceeds the above range, there is a possibility that defects such as scratches may be generated on the polishing object or the polishing performance may be reduced.

[0159] Furthermore, the polishing sheet of the present invention can be used for silicon oxide (SiO x The above-mentioned grinding flatness can be obtained by the grinding flatness formula proposed above.

[0160] Specifically, for silicon oxide (SiO x ) The grinding flatness of the above-mentioned grinding sheet can be less than 5.5%, less than 5.4%, less than 5.3%, less than 5.2%, or less than 5.0%, but is not limited thereto.

[0161] If the polishing flatness of the polishing sheet reaches the above range, it is easy to polish the surface of the polishing object that requires high surface flatness, and a semiconductor device with excellent quality can be provided.

[0162] The constituent components and physical properties of the above-mentioned polishing sheets can be combined with each other.

[0163] <Abrasive Sheet Manufacturing Method>

[0164] A method for manufacturing an abrasive sheet in one embodiment includes the following steps: preparing a composition by sequentially or simultaneously mixing a urethane prepolymer, a curing agent, and a foaming agent; and curing the composition by injecting it into a mold to form an abrasive layer.

[0165] The urethane prepolymer may include a prepolymerization reaction product of one or more isocyanate compounds and one or more polyols. The description of the isocyanate compound and the polyol is the same as that described above.

[0166] Furthermore, according to the requirements, an additive including a surfactant may be added to the above composition. The description of the above surfactant is the same as that described above.

[0167] As an example, the urethane prepolymer, the curing agent, and the blowing agent may be added substantially simultaneously in the mixing step. When the blowing agent, the surfactant, and the inert gas are also added, these may also be added substantially simultaneously in the mixing step.

[0168] As another example, the urethane prepolymer, the foaming agent, and the surfactant may be mixed in advance, and then the curing agent may be added, or the curing agent and the inert gas may be added simultaneously.

[0169] The mixing can be performed at a speed of 1000 rpm to 10000 rpm or 4000 rpm to 7000 rpm. When the speed reaches the above range, it is more conducive to uniformly dispersing the inert gas and the foaming agent in the composition.

[0170] Furthermore, the step of preparing the composition may be performed at a temperature of 50° C. to 150° C., and may be performed under vacuum degassing conditions as required.

[0171] The step of injecting the above composition into the mold to solidify and form the grinding layer can be carried out at a temperature of 60° C. to 150° C. and a pressure of 50 kg / m 2 Up to 260kg / m 2 performed under pressure conditions.

[0172] Furthermore, the preparation method may further include the steps of cutting the surface of the obtained abrasive sheet, processing grooves on the surface, bonding the abrasive sheet with a cushion layer, inspecting the abrasive sheet, packaging the abrasive sheet, etc. These steps may be performed in a conventional abrasive sheet manufacturing method.

[0173] The description of the polishing sheet manufactured by the above-mentioned manufacturing method is the same as that described above.

[0174] By manufacturing the above-mentioned grinding sheet according to the above-mentioned manufacturing method, excellent performance can be shown in terms of grinding rate and grinding flatness. In addition, defects such as scratches on the grinding object can be minimized, the grinding performance can be maintained at a constant level, and not only that, the life of the grinding sheet can be increased. Therefore, it is convenient to grind materials that require high surface flatness such as silicon wafers for semiconductor devices, and semiconductor devices such as semiconductor substrates with excellent quality can be provided.

[0175] <Method for manufacturing semiconductor device>

[0176] A method for manufacturing a semiconductor device according to an example includes the step of polishing a surface of a semiconductor substrate using the polishing sheet according to an example.

[0177] Specifically, a manufacturing method of a semiconductor device of an example includes the following steps: preparing a grinding sheet including a stacked body consisting of a grinding layer, a bonding layer and a cushion layer; and relatively rotating the grinding sheet so that the grinding layer surface of the grinding sheet contacts the surface of a wafer and thereby grinding the surface of the wafer, wherein the initial load resistance LR of the stacked body is defined by the following formula 1: L Reaching over 88%.

[0178] <Formula 1>

[0179]

[0180] In the above formula 1, T1 L is the thickness of the laminate under no-load conditions, T2 L T3 is the thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. L For the above T2 L The thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds.

[0181] Another example of a method for manufacturing a semiconductor device includes the following steps: preparing a grinding sheet including a grinding layer and a cushion layer; and relatively rotating the grinding sheet so that the grinding layer surface of the grinding sheet contacts the surface of a wafer and thereby grinding the surface of the wafer, wherein the cushion layer has an initial load resistance LR defined by the following formula 5: C Reach more than 45%.

[0182] <Formula 5>

[0183]

[0184] In the above formula 5, T1 C is the thickness of the cushion layer under no-load condition, T2 C T3 is the thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. C For the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds.

[0185] Figure 1 A schematic process diagram showing a semiconductor device manufacturing process of an example. Figure 1After the polishing sheet 110 of the above-mentioned example is mounted on the fixed plate 120, the semiconductor substrate 130 is arranged on the above-mentioned polishing sheet 110. In this case, the surface of the above-mentioned semiconductor substrate 130 is in direct contact with the polishing surface of the above-mentioned polishing sheet 110. In order to perform polishing, the polishing slurry 150 can be sprayed onto the above-mentioned polishing sheet through the nozzle 140. The flow rate of the polishing slurry 150 supplied through the above-mentioned nozzle 140 can be about 10cm 3 / min to about 1000cm 3 / minute range is selected as needed, for example, it can be about 50cm 3 / min to about 500cm 3 / minute, but is not limited thereto.

[0186] Afterwards, the surface of the semiconductor substrate 130 may be ground by rotating the semiconductor substrate 130 and the grinding sheet 110 relative to each other. In this case, the rotation direction of the semiconductor substrate 130 and the rotation direction of the grinding sheet 110 may be the same direction or opposite directions. The rotation speed of the semiconductor substrate 130 and the grinding sheet 110 may be selected as needed within the range of about 10 rpm to about 500 rpm, for example, about 30 rpm to about 200 rpm, but is not limited thereto.

[0187] The semiconductor substrate 130 can be mounted on the polishing head 160 and a predetermined load can be applied to the polishing surface of the polishing sheet 110 to achieve contact, thereby polishing the surface of the semiconductor substrate 130. The load applied to the polishing surface of the polishing sheet 110 by the polishing head 160 can be about 1 gf / cm 2 To about 1000gf / cm 2 The range can be selected as needed, for example, it can be about 10gf / cm 2 To about 800gf / cm 2 , but is not limited to this.

[0188] In one example, the method for manufacturing the semiconductor device may further include the following step, namely, in order to maintain the grinding surface of the grinding sheet 110 in a state suitable for grinding, the grinding surface of the grinding sheet 110 is processed by the regulator 270 while the semiconductor substrate 130 is being ground.

[0189] The abrasive sheet of the above example can be obtained by controlling the initial load resistance LR of the liner layer and the laminate. C and initial load resistance LR LTo improve the grinding rate and grinding flatness of silicon oxide and tungsten, the above-mentioned grinding sheet can be used to effectively manufacture semiconductor devices with excellent quality.

[0190] The above contents are described in more detail by the following examples. However, the following examples are merely illustrative of the present invention, and the scope of the examples is not limited thereto.

[0191] <Example>

[0192] Example 1

[0193] 1-1: Device structure

[0194] In a casting device provided with injection lines for urethane prepolymer, curing agent, inert gas, and reaction rate regulator, a prepolymer composition containing unreacted NCO at a content of 9.1 weight percent (SKC) was filled into the prepolymer tank, 4,4'-diamino-3,3'-dichlorodiphenylmethane (bis(4-amino-3-chlorophenyl)methane, Ishihara) was filled into the curing agent tank, and nitrogen (N2) was prepared as an inert gas. In addition, 1 weight part of a solid phase foaming agent (manufacturer: Akzonobel) and 1 weight part of a silicone surfactant (Evonik) were premixed with 100 weight parts of the above urethane prepolymer and then injected into the prepolymer tank.

[0195] 1-2: Manufacturing of abrasive sheets

[0196] The raw materials are fed into the stirring head at a specified speed through the respective feeding pipelines and stirred. In this case, the prepolymer and the curing agent are fed at an equivalent ratio of 1:1. Nitrogen (N2) as an inert gas is fed at a rate of 1L / min. The stirred raw materials are discharged into a mold (1000mm×1000mm×3mm) preheated at a temperature of 120°C, and after injection at a discharge rate of 10kg / min, casting is performed at a temperature of 120°C to obtain a molded body. Afterwards, the upper and lower ends of the above-mentioned molded body are cut at a thickness of 0.5mm, respectively, to obtain a grinding layer with a thickness of 2mm.

[0197] Furthermore, as a backing layer in which a polyester fiber nonwoven fabric is impregnated with a polyurethane resin, in particular, a backing layer having a hardness, thickness, initial load resistance and compression elastic modulus reaching the levels shown in the following Table 1 is selected to attach the above-mentioned grinding layer and the above-mentioned backing layer using a hot melt adhesive, thereby manufacturing a grinding sheet.

[0198] Example 2

[0199] A polishing sheet was manufactured in the same manner as in Example 1, except that a cushion layer having hardness, thickness, initial load resistance and compression modulus at the levels shown in Table 1 below was selected and used.

[0200] Example 3

[0201] 2-1: Device structure

[0202] In the casting device in Example 1, the inert gas injection line was blocked. The prepolymer tank was filled with PUGL-600D (SKC product, weight average molecular weight: 1500 g / mol) to 9.1 NCO%, and the curing agent tank was filled with 4,4'-methylenebis(2-chloroaniline) (TCI, Tokyo Chemical Industry product). Furthermore, 2 parts by weight of a solid phase foaming agent (Akzonobel) was premixed with 100 parts by weight of the urethane prepolymer and then injected into the prepolymer tank.

[0203] 2-2: Manufacturing of abrasive sheets

[0204] The raw materials were fed into the stirring head at a specified speed through the respective feeding lines and stirred. In this case, the prepolymer and the curing agent were fed at an equivalent ratio of 1:1. The stirred raw materials were discharged into a mold (1000mm×1000mm×3mm) preheated at a temperature of 120°C, and after injection at a discharge rate of 10kg / min, casting was performed at a temperature of 120°C to manufacture a molded body. Thereafter, the upper and lower ends of the above-mentioned molded body were cut at a thickness of 0.5mm, respectively, to obtain a grinding layer with a thickness of 2mm.

[0205] Furthermore, as a backing layer in which a polyester fiber nonwoven fabric is impregnated with a polyurethane resin, in particular, a backing layer having a hardness, thickness, initial load resistance and compression elastic modulus reaching the levels shown in the following Table 1 is selected to attach the above-mentioned grinding layer and the above-mentioned backing layer using a hot melt adhesive, thereby manufacturing a grinding sheet.

[0206] Example 4

[0207] A polishing sheet was manufactured in the same manner as in Example 3, except that a cushion layer having hardness, thickness, initial load resistance and compression modulus at the levels shown in Table 1 below was selected and used.

[0208] Comparative Example 1

[0209] A polishing sheet was manufactured in the same manner as in Example 1, except that a cushion layer having hardness, thickness, initial load resistance and compression modulus at the levels shown in Table 1 below was selected and used.

[0210] Comparative Example 2

[0211] A polishing sheet was manufactured in the same manner as in Example 3, except that a cushion layer having hardness, thickness, initial load resistance and compression modulus at the levels shown in Table 1 below was selected and used.

[0212] Example 5

[0213] A polishing layer was obtained by the same method as in Example 1 above.

[0214] Afterwards, as a backing layer in which a polyester fiber nonwoven fabric is impregnated with a polyurethane resin, in particular, a backing layer in which the screening hardness reaches the level shown in the following Table 2, the above-mentioned grinding layer and the above-mentioned backing layer are attached using a hot melt adhesive, thereby manufacturing a grinding sheet including a laminate having a thickness, initial load resistance and compression elastic modulus reaching the levels shown in the following Table 2.

[0215] Example 6

[0216] The stirred raw material is discharged into a mold (1000mm×1000mm×3mm) preheated at 80°C, and after injection at a discharge rate of 10kg / min, casting is performed at 120°C to obtain a molded body. A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached using a hot melt adhesive to manufacture a grinding sheet including a stacked body having a thickness, initial load resistance and compression elastic modulus reaching the levels shown in the following Table 2. Except for the above content, the grinding sheet is manufactured by the same method as the above-mentioned Example 5.

[0217] Example 7

[0218] A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached to each other using a hot-melt adhesive, thereby manufacturing a grinding sheet including a stacked body having a thickness, initial load resistance rate and compression elastic modulus reaching the level shown in the following Table 1. Except for the above content, the grinding sheet is manufactured by the same method as the above-mentioned Example 5.

[0219] Example 8

[0220] A polishing layer was obtained by the same method as in Example 4 above.

[0221] Afterwards, as a backing layer in which a polyester fiber nonwoven fabric is impregnated with a polyurethane resin, in particular, a backing layer in which the screening hardness reaches the level shown in the following Table 2, the above-mentioned grinding layer and the above-mentioned backing layer are attached using a hot melt adhesive, thereby manufacturing a grinding sheet including a laminate having a thickness, initial load resistance and compression elastic modulus reaching the levels shown in the following Table 2.

[0222] Example 9

[0223] The stirred raw material is discharged into a mold (1000mm×1000mm×3mm) preheated at 80°C, and after being injected at a discharge rate of 10kg / min, it is cast at 120°C to manufacture a molded body. A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached using a hot-melt adhesive to manufacture a grinding sheet including a stacked body having a thickness, initial load resistance and compression elastic modulus reaching the levels shown in Table 2. Except for the above content, the grinding sheet is manufactured in the same manner as in the above-mentioned Example 8.

[0224] Example 10

[0225] A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached using a hot melt adhesive, thereby manufacturing a grinding sheet including a stacked body having a thickness, initial load resistance and compression elastic modulus reaching the level shown in the following Table 2. Except for the above content, the grinding sheet is manufactured by the same method as the above-mentioned Example 8.

[0226] Comparative Example 3

[0227] A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached to each other using a hot-melt adhesive, thereby manufacturing a grinding sheet including a stacked body having a thickness, an initial load resistance rate and a compression elastic modulus reaching the level shown in the following Table 2. Except for the above content, the grinding sheet is manufactured by the same method as the above-mentioned Example 5.

[0228] Comparative Example 4

[0229] A backing layer having a hardness reaching the level shown in the following Table 2 is screened and prepared, and the above-mentioned grinding layer and the above-mentioned backing layer are attached to each other using a hot-melt adhesive, thereby manufacturing a grinding sheet including a stacked body having a thickness, an initial load resistance rate and a compression elastic modulus reaching the level shown in the following Table 2. Except for the above content, the grinding sheet is manufactured by the same method as the above-mentioned Example 8.

[0230] <Evaluation Example>

[0231] The following physical properties were measured and evaluated for the polishing sheets produced in Examples 1 to 10 and Comparative Examples 1 to 4, and the results are shown in Tables 1 and 2 below.

[0232] Evaluation Example 1: Hardness

[0233] The cushion layer sample was cut into a size of 5 cm×5 cm (thickness: shown in Tables 1 and 2), stored at a temperature of 25° C. for 12 hours, and then measured for Asker C hardness using a hardness tester.

[0234] Evaluation Example 2: Initial load resistance (%)

[0235] The cushion layer sample and the laminate sample were cut into a size of 5 cm × 5 cm (thickness: shown in Table 1 and Table 2), and the thickness of the cushion layer and the thickness of the laminate under no load were measured and set as T1 and T2, respectively. C (mm) and T1 L The thickness of the liner layer and the thickness of the laminated body when the stress load of 30 kPa is maintained for 60 seconds from the no-load state are measured and are set as T2 C (mm) and T2 L (mm), measured from the above T2 C and T2 L The thickness of the liner layer and the thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds are respectively referred to as T3. C (mm) and T3 L (mm), and then the initial load resistance (LR) was calculated according to the following formula 1 and formula 5 C LR L ).

[0236] <Formula 1>

[0237]

[0238] <Formula 5>

[0239]

[0240] Evaluation Example 3: Compression elasticity (%)

[0241] The cushion layer sample and the laminate sample were cut into a size of 5 cm × 5 cm (thickness: shown in Table 1 and Table 2), and the thickness of the cushion layer and the thickness of the laminate were measured when a stress load of 30 kPa was maintained for 60 seconds from a no-load state, and were set as T2 C (mm) and T2 L (mm), measured from the above T2 C and T2 L The thickness of the liner layer and the thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds are respectively referred to as T3. C (mm) and T3 L (mm), measured from the above T3 C and T3 LThe stress load is eliminated in each state and after being left for 60 seconds, 30 kPa (300 g / cm 2 The thickness of the liner layer and the thickness of the laminated body when the stress load is 400 ℃ and 1000 ℃ respectively are set as T4 C (mm) and T4 L (mm), and then the compression modulus (CE C ,CE L ).

[0242] <Formula 2>

[0243]

[0244] <Formula 6>

[0245]

[0246] Evaluation Example 4: Elastic modulus

[0247] The abrasive sheet samples were cut into a size of 4 cm×1 cm (thickness: shown in Tables 1 and 2), and the modulus was measured using a universal testing machine (UTM) at a speed of 50 mm / min using the slope connecting the line at 70% elongation and the line at 20% elongation.

[0248] Evaluation Example 5: Polishing Rate

[0249] The polishing rates of Examples 1 to 4 and Comparative Examples 1 and 2 were evaluated by the following method.

[0250] A silicon wafer with a diameter of 300 mm on which a tungsten (W) film was formed by a chemical vapor deposition (CVD) process was placed using a single chip multiprocessor (CMP) polishing device. Then, a silicon oxide (SiO2) film was formed by a TEOS-plasma chemical vapor deposition process on a platen with the polishing sheet attached. x ) film with a diameter of 300mm. Then, on the fixed plate with the above-mentioned grinding sheet, it is set in a manner that the silicon oxide film of the silicon wafer faces downward. Then, the grinding load is adjusted to reach 1.4psi, and the sintered silicon slurry is added to the grinding sheet at a speed of 190ml / min and the fixed plate is rotated at a speed of 115rpm for 60 seconds to grind the silicon oxide film. After grinding, the silicon wafer is separated from the carrier and installed in a spin dryer (spin dryer) and cleaned with deionized water (DIW), and then dried with air for 15 seconds. The thickness difference before and after grinding is measured on the dried silicon wafer using a light interference thickness measuring device (manufacturer: Kyence Company; model: SI-F80R). Then, the grinding rate is calculated using the following formula.

[0251]

[0252] Evaluation Example 6: Polishing Rate

[0253] For Examples 5 to 10, Comparative Examples 3 and 4, the polishing rates were evaluated by the following method.

[0254] A silicon wafer with a diameter of 300 mm on which a tungsten (W) film is formed by a chemical vapor deposition process is set using a single-chip multi-processor grinding device. Afterwards, on a fixed plate with the above-mentioned grinding sheet, the tungsten (W) film of the silicon wafer is set to face downward. Afterwards, the grinding load is adjusted to 2.8 psi, and sintered silicon slurry is added to the grinding sheet at a speed of 190 ml / min and the fixed plate is rotated at a speed of 115 rpm for 30 seconds to grind the tungsten (W) film. After grinding, the silicon wafer is separated from the carrier and installed in a rotary dehydrator and cleaned with deionized water, and then dried with air for 15 seconds. The thickness difference before and after grinding is measured for the dried silicon wafer using a contact surface resistance measuring device (4 point probe). Afterwards, the grinding rate is calculated using the grinding rate formula in Evaluation Example 5.

[0255] Evaluation Example 7: Grinding Flatness

[0256] The polishing rate was measured in the same manner as in the above-mentioned Evaluation Example 5 using a silicon oxide (SiO x ) film and coated with A silicon wafer with a thermal oxide film was polished for 1 minute under the above polishing conditions, and then the film thickness in the surface of the wafer was measured at 98 locations and the polishing flatness (WIWNU: Within Wafer Non Uniformity) in the surface of the wafer was measured using the following formula.

[0257] Furthermore, the polishing flatness of the silicon wafer on which the tungsten (W) film was formed, which was obtained by the same method as the polishing rate measurement in Evaluation Example 6, was also measured by the same method.

[0258]

[0259] Table 1

[0260]

[0261] Table 2

[0262]

[0263] As shown in Table 1 and Table 2, it can be confirmed that the polishing sheets of Examples 1 to 10 have better polishing rates and polishing flatness than the polishing sheets of Comparative Examples 1 to 4.

Claims

1. A grinding sheet, characterized in that: The invention comprises a laminated body consisting of a grinding layer, a bonding layer and a cushion layer, The initial load resistance LR of the laminate is defined by the following formula 1: L More than 88%, <Formula 1> In the above formula 1, T1 L is the thickness of the laminate under no-load conditions, T2 L The thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. T3 L From the above T2 L The thickness of the laminate when the state is maintained at a stress load of 50 kPa for 60 seconds; Hardness of the cushion layer L 68Asker C to 74Asker C; Elastic modulus L 100kgf / cm 2 Up to 160kgf / cm 2 .

2. The abrasive sheet according to claim 1, characterized in that: The compressive modulus CE of the laminate is defined by the following formula 2: L More than 50%, <Formula 2> In the above formula 2, T2 L The thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. T3 L From the above T2 L The thickness of the laminate when the stress load of 50 kPa is maintained for 60 seconds, T4 L For the above T3 L The thickness of the laminate when the stress load is removed and the laminate is left to stand for 60 seconds and then the stress load of 30 kPa is maintained for 60 seconds.

3. The abrasive sheet according to claim 1, characterized in that: The thickness T1 of the laminate under no load L 2.0mm to 4.5mm.

4. The abrasive sheet according to claim 1, characterized in that: The grinding rate for tungsten is the following, The polishing flatness WIWNU of tungsten is 4.3% or less.

5. The abrasive sheet according to claim 1, characterized in that: The grinding layer comprises a cured product of a composition comprising a urethane prepolymer, a curing agent and a foaming agent. The above-mentioned abrasive sheet satisfies at least one of the following i), ii) and iii): i) the urethane prepolymer comprises a prepolymerization reaction product of one or more isocyanate compounds and one or more polyols; ii) the curing agent is one or more selected from the group consisting of amine compounds and alcohol compounds; iii) The foaming agent is at least one selected from the group consisting of a solid-phase foaming agent and a gas-phase foaming agent.

6. A grinding sheet, characterized in that: Including grinding layer and cushion layer, The initial load resistance LR of the cushion layer is defined by the following formula 5: C More than 45%, <Formula 5> In the above formula 5, T1 C is the thickness of the cushion layer under no-load condition, T2 C The thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. T3 C From the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds; Hardness of the cushion layer c 69Asker C to 80Asker C; Elastic modulus of abrasive sheet C 100kgf / cm 2 Up to 170kgf / cm 2 .

7. The abrasive sheet according to claim 6, characterized in that: The compressive elastic modulus CE of the cushion layer is defined by the following formula 6: C Less than 90%, <Formula 6> In the above formula 6, T2 C The thickness of the cushion layer when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. T3 C From the above T2 C The thickness of the cushion layer when the stress load of 50 kPa is maintained for 60 seconds, T4 C For the above T3 C After the stress load is removed and left for 60 seconds, 30 kPa (300 g / cm 2 ) is the thickness of the cushion layer when the stress load is greater than .

8. A method for manufacturing a semiconductor device, characterized in that: include: The step of preparing an abrasive sheet including a laminate composed of an abrasive layer, an adhesive layer and a cushion layer; as well as The step of grinding the surface of the wafer by relatively rotating the grinding sheet so that the grinding layer surface of the grinding sheet contacts the surface of the wafer, The initial load resistance LR of the laminate is defined by the following formula 1: L More than 88%, <Formula 1> In the above formula 1, T1 L is the thickness of the laminate under no-load conditions, T2 L The thickness of the laminate when a stress load of 30 kPa is maintained for 60 seconds from a no-load state. T3 L From the above T2 L The thickness of the laminate when the state is maintained at a stress load of 50 kPa for 60 seconds; Hardness of the cushion layer L 68Asker C to 74Asker C; Elastic modulus L 100kgf / cm 2 Up to 160kgf / cm 2 .

Citation Information

Patent Citations

  • Polishing pad and method for manufacturing semiconductor device

    US20060037699A1